2021
DOI: 10.47108/jidhealth.vol4.iss2.120
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography assessment of the ethmoid roof based on Keros classification in Iraqi patients undergoing functional endoscopic sinus surgery

Abstract: Background: Among the most popular methods employed to classify the depth of the olfactory fossa is Keros classification. This study aims to assess Keros classification of the ethmoid roof, any possible association between Keros types and gender, and the incidence of asymmetry between right and left sides among Iraqi patients.  Methods: A retrospective cross-sectional study was conducted at Al-Shaheed Gazi Al-Hariri Teaching Hospital, Medical City, Baghdad, Iraq. The archived reports and the CT scans ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was conducted at Department of Radiology, Ziauddin University, after the approval from ethics review committee. (14) Patients without any sphenoid sinus abnormality or adjacent structures coming for brain and head CT scan were part of this study. 16 slice Toshiba Alexion CT scanner was used to perform the scans.…”
Section: Methodsmentioning
confidence: 99%
“…It was conducted at Department of Radiology, Ziauddin University, after the approval from ethics review committee. (14) Patients without any sphenoid sinus abnormality or adjacent structures coming for brain and head CT scan were part of this study. 16 slice Toshiba Alexion CT scanner was used to perform the scans.…”
Section: Methodsmentioning
confidence: 99%
“…Elwany et al (18) reported that type 2 OF was the most common type in males, while type 1 was most common in females. Murthy and Santosh (29) and Abdulhadi et al (31) evaluated CT images of patients undergoing FESS and reported type 2 and type 1 as the most frequent types, respectively.In contrast, Gauba et al (32) reported that type 3 was slightly high. Babu et al (25) reported that the mean OF depths on the right and left sides were 5.27 mm and 5.25 mm, respectively.…”
Section: Of Types According To Depth Measurementsmentioning
confidence: 99%